Pengaruh Motivasi Dan Disiplin Kerja Terhadap Kinerja Karyawan Pada PT Hasnur Riung Sinergi Tapin - yuliani yuliani; Sasna Maudi Abdelian (Economy Deposit Journal (E-DJ), 2022)
The research to determine how the nfluence of motivation and work discipline on employee performance at PTHasnur Riung Sinergi Tapin. The results of the study indicate that there are still employees who lack discipline, especially on timeliness of work attendance. Although there are some employees who still lack work discipline, the performance of employees in this company has carried out their performance well. After analyzing and discussing the problem, the author concludes that the Ef ect of Motivation and Work Discipline on Employee Performance at PT Hasnur Riung Sinergi Tapin is still not exactly work discipline on its performance, this PT Hasnur Riung Sinergi Tapin still needs to improve its performance fromthe one so that can get better company performance